KOORDINASI DALAM PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KABUPATEN INDRAGIRI HILIR TAHUN 2019 - Ryan Anugerah Putra; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Corporate Social Responsibility (CSR) is a corporate social program to provide assistance and empower the community around the company as a form of social responsibility or compensation for things lost from the community because of the operation of the company. The problem contained in this study is that there are still many companies that have not reported the results of CSR activities to the Local Government or CSR Forum and supervision conducted by the Regional Government of Indragiri Hilir Regency has not been maximized. The formulation of this research problem is How to Coordinate in the Implementation of Corporate Social Responsibility (CSR) Program in Indragiri Hilir District in 2019, and What are the Coordination Constraints in the Implementation of Corporate Social Responsibility (CSR) Program in Indragiri Hilir District in 2019. The purpose of this study is to describe coordination in the implementation of Corporate Social Responsibility (CSR) program in Indragiri Hilir Regency in 2019 and to know the coordination constraints in the implementation of corporate social responsibility (CSR) program in Indragiri Hilir regency in 2019. The research approach used is qualitative approach. This type of research is descriptive. The research location is in Indragiri Hilir Regency. The type and source of research data is divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to CSR implementation. Data collection techniques are used by interviews and documentation. While the data analysis is done using qualitative analysis. The result of this research is coordination in the Implementation of Corporate Social Responsibility (CSR) Program in Indragiri Hilir Regency in 2019 has been carried out, related to its coordiansi can be seen from 4 basic coordination, namely: cooperation, division of tasks, communication and meeting meetings. Constraints in coordinating the implementation of CSR programs in Indragiri Hilir Regency, among others, there are still some pokja that do not run to the maximum and have not been formed a Supervisory Team in accordance with existing regulations. Keywords: Coordination, Corporate Social Responsibiliity (CSR)